Characteristics of the qualification of exceeding authority or official authority by a military official personal by subjective characters - A. A. Sakovskyi; I. I. Kostiuk (Bulletin of Kharkiv National University of Internal Affairs)
The relevance of the research topic is due to the need to improve the legal regulation of the activities of military personnel in the context of the modern political, social and military situation, which requires careful consideration of issues related to their compliance with the law and the preservation of law and order. The main purpose of the study is to analyze and clarify the criteria for the legal qualification of exceeding the power or official authority of a military official on subjective grounds. Within the framework of this analysis, subjective signs of exceeding power or official authority are considered, in particular, awareness of the socially dangerous nature of the committed actions, the compliance of these actions with regulatory and legal acts, the consequences of violations and their connection with the official position. The study also considers the possibility of the emergence of an ideal set of criminal composition in case of committing several offenses in one act. The obtained conclusions will contribute to clarifying the qualification of offenses and understanding the ratio of illegal actions of a military official and their consequences. The methodological basis of the research is based on the analysis of normative legal acts, law enforcement and jurisprudential analysis, as well as on the analysis of judicial practice. The use of these methods allows for a detailed analysis of issues related to the legal qualification of the criminal offense provided for in Art. 426-1 of the Criminal Code of Ukraine. The results of the study can be useful for legislators, law enforcement agencies, military groups and judicial authorities. They will help to improve the legal regulation of the activities of military officials, ensuring the preservation of law and order and legality in this area of legal relations. The practical significance of this study also lies in the correct application of the norms of criminal legislation during the investigation of the abuse of power or official authority by a military official. In the conclusions, it is proposed to supplement Art. 426-1 of the Criminal Code of Ukraine.